ABANDONMENT OF SOD-CUTTING MAY CAUSE LOSS OF CHARACTERISTICS HEATHLAND COMMUNITIES -THE CASE OF A MILITARY TRAINING AREA IN THE NETHERLANDS - HAVEMAN, R.; VAN DER BERG, A.; VAN DER WIJNGAART, R. (Annali di Botanica, 2005)